The mixed randomized trial: combining randomized, pragmatic and observational clinical trial designs. (November 2016) - Alsop, Jonathan; Scott, Martin; Archey, William
Clinical trial designs often fail to deliver data that jointly satisfy evolving demands of both regulatory and reimbursement authorities. We propose a new multi-tiered trial design to integrate efficacy and effectiveness, and address the evolving needs of authorities. The mixed randomized trial allocates patients first to trial arm – randomized controlled, pragmatic (randomized) or observational – and then to treatment group – experimental, placebo, active comparator, best available therapy or standard of care. Trial arms may be staggered over time to reflect the current state of randomized and non-randomized data of the experimental drug, and thereby still prioritize safety. At the same time, the mixed randomized trial allows for the collection of real-world data in a randomized setting, and thereby reduces selection bias.